2024
DOI: 10.3389/fncel.2024.1323986
|View full text |Cite
|
Sign up to set email alerts
|

Neuropeptide Y receptor 1 and galanin receptor 2 (NPY1R-GALR2) interactions in the dentate gyrus and their relevance for neurogenesis and cognition

Rasiel Beltran-Casanueva,
Aracelis Hernández-García,
Paula de Amo García
et al.

Abstract: IntroductionThis study may unveil novel insights into the interactions between neuropeptide Y receptor 1 (NPY1R) and galanin receptor 2 (GALR2), in the dentate gyrus of the dorsal hippocampus, shedding light on their role in neurogenesis and cognitive functions. Existing literature highlights the potential of these interactions in enhancing learning and memory, yet detailed mechanisms remain underexplored.MethodsUtilizing intracerebroventricular injections of GALR2 and NPY1R agonists in Sprague-Dawley male rat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2025
2025

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 59 publications
0
1
0
Order By: Relevance
“…Subsequent study revealed a sustained increase in neurogenesis in the dorsal dentate gyrus following ICV administration of GALR2 and NPY1R agonists. Simultaneous delivery of the M1145 and the NPY1R agonist promoted neuroblast proliferation and improvement in object-in-place memory [ 69 ]. Additionally, galanin receptor-2/3 agonist (Gal 2-11) induced proliferation of hippocampal precursor cells, thus directly affected hippocampal neurogenesis, impaired in AD, through production of granule cell neurons of the dentate gyrus [ 70 ].…”
Section: Orexigenic Neuropeptidesmentioning
confidence: 99%
“…Subsequent study revealed a sustained increase in neurogenesis in the dorsal dentate gyrus following ICV administration of GALR2 and NPY1R agonists. Simultaneous delivery of the M1145 and the NPY1R agonist promoted neuroblast proliferation and improvement in object-in-place memory [ 69 ]. Additionally, galanin receptor-2/3 agonist (Gal 2-11) induced proliferation of hippocampal precursor cells, thus directly affected hippocampal neurogenesis, impaired in AD, through production of granule cell neurons of the dentate gyrus [ 70 ].…”
Section: Orexigenic Neuropeptidesmentioning
confidence: 99%